Time of the day of exercise impact on cardiovascular disease risk factors in adults: a systematic review and meta-analysis. Issue 3 (March 2023) - Sevilla-Lorente, R.; Carneiro-Barrera, A.; Molina-Garcia, P.; Ruiz, J.R.; Amaro-Gahete, F.J.
Abstract: Objectives: To compare the effect of a single bout of morning vs. evening exercise on cardiovascular risk factors in adults. Design: Systematic review and meta-analysis. Methods: A systematic search of studies was conducted using PubMed and Web of Science from inception to June 2022. Selected studies accomplished the following criteria: crossover design, acute effect of exercise, blood pressure, blood glucose, and/or blood lipids as the study's endpoint, a washout period of at least 24 h, and adults. Meta-analysis was performed by analyzing: 1) separated effect of morning and evening exercise (pre vs. post); and 2) comparison between morning and evening exercise. Results: A total of 11 studies were included for systolic and diastolic blood pressure and 10 studies for blood glucose. Meta-analysis revealed no significant difference between morning vs. evening exercise for systolic blood pressure (g ∆ = 0.02), diastolic blood pressure (g ∆ = 0.01), or blood glucose (g ∆ = 0.15). Analysis of moderator variables (age, BMI, sex, health status, intensity and duration of exercise, and hour within the morning or evening) showed no significant morning vs. evening effect. Conclusions: Overall, we found no influence of the time of the day on the acute effect of exercise on blood pressure neither on blood glucose.